Exploring the effect of axial ligand substitution (X = Br, NCS, CN) on the photodecomposition and electrochemical activity of [MnX(N–C)(CO)3] complexes. Issue 5 (15th December 2014) - Agarwal, Jay; Stanton III, Charles J.; Shaw, Travis W.; Vandezande, Jonathon E.; Majetich, George F.; Bocarsly, Andrew B.; Schaefer III, Henry F.
Abstract : Four new Mn(i )-NHC compounds are tested for light stability and catalytic efficiency for reducing CO2 to CO. Abstract : The synthesis, electrochemical activity, and relative photodecomposition rate is reported for four new Mn(i ) N -heterocyclic carbene complexes: [MnX( N -ethyl- N ′-2-pyridylimidazol-2-ylidine)(CO)3 ] (X = Br, NCS, CN) and [MnCN( N -ethyl- N ′-2-pyridylbenzimidazol-2-ylidine)(CO)3 ]. All compounds display an electrocatalytic current enhancement under CO2 at the potential of the first reduction, which ranges from −1.53 V to −1.96 V versus the saturated calomel electrode. Catalytic CO production is observed for all species during four-hour preparative-scale electrolysis, but substantial H2 is detected in compounds where X is not Br. All species eventually decompose under both 350 nm and 420 nm light, but cyanide substituted complexes (X = CN) last significantly longer (up to 5×) under 420 nm light as a result of a blue-shifted MLCT band.